What my father and I don't talk about : sixteen writers break the silence - Filgate, Michele; Altschul, Andrew Foster; Buntin, Julie; Castle, Jiordan; Darraj, Susan Muaddi; Díaz, Jaquira; Landis, Dylan, 1956-; Marzano-Lesnevich, Alexandria; McElroy, Isle; McMasters, Kelly; Morín, Tomás Q.; Munaweera, Nayomi; et al. (What we don't talk about, 2025)
"A follow-up to 'What My Mother and I Don't Talk About', this collection of essays from 16 notable writers breaks the silence on the complex--and sometimes contentious--relationships we have with our fathers. A viral sensation online, this is an essential collection that dives into the personal and poignant topics we often struggle to discuss with those who are meant to know and love us best"--